Microsponge as a Strategy for Effective Drug Delivery System - Nora Zawar. Yousif; Zeina D Salman (Al Mustansiriyah Journal of Pharmaceutical Sciences, 2023)
The technology of drug delivery has become massively competitive and quickly growing. Enhancing efficacy is the primary objective of delivery system development, and hence cost-effectiveness of the treatment. Nevertheless, controlling the rate of delivery of active pharmaceutical moieties to a target site within the body has been one of the major obstacles confronted by the drug industry. Microsponge represents a delivery system considered a promising innovation that overcomes the different challenges, since, this dosage form provides the delivery of active pharmaceutical moieties in a timely manner, in addition to responding to different stimuli (pressure, temperature, pH). Microsponge drug delivery technology proposed capturing of active moieties into tiny spongy spheres thus, donating towards reducing side effects, improving stability, increasing elegance, and enhancing formulation flexibility. The goal behind this contribution is to cover microsponge as a successful innovation, summarizing the characteristics, advantages, and limitations with certain insight into the mechanism and factors triggering the release. Furthermore, shed light on the methodology of preparation.